Price Exploration of Various Insecticide Groups, Their Registered Crops and Insect Pest Species for Farmers’ - Ignatius Putra Andika; Reza Fikri Alfaatah (Universitas Muhammadiyah Jember, 2022)
Insecticides are hazardous substance that are often used in agriculture to reduce yield loss due to insect pest. Overuse of insecticide may result in detrimental effects to the environment and human health; thus, its use should be limited. Indonesian farmers still use insecticide making studies of their use to be required, especially on how farmers choose their insecticides. This study aimed to explore the price differences of insecticide based on insecticide group and their registered insect species and crops. Insecticide brands officially registered to the Ministry of Agriculture of Republic Indonesia were used in this study together with prices collected from the internet. Analysis was done for the top 10 crops registered by formulators, including chili pepper, shallot, rice, soybean, cabbage, cacao, palm oil, tomato, potato, and corn. Results showed that there were insignificant correlations between package and application price for most crops in this study, except cabbage and tomatoes. However, insecticides belonging to pyrethroid, organophosphate, and carbamate were clustered in an area of low application and package prices. Explorations based on insect species also showed that certain groups were cheaper than others when farmers are using insecticide at recommended dosages or concentrations and also according to registered crop and pest species. Price may become a factor for farmers to help decide what product. Therefore, there a merit further understanding currently distributed products while safer and novel management strategies are being developed and disseminated to farmers.